2022
DOI: 10.1097/j.pain.0000000000002834
|View full text |Cite
|
Sign up to set email alerts
|

AIBP regulates TRPV1 activation in chemotherapy-induced peripheral neuropathy by controlling lipid raft dynamics and proximity to TLR4 in dorsal root ganglion neurons

Abstract: Supplemental Digital Content is Available in the Text.Intrathecal Apolipoprotein A-I binding protein reverses paclitaxel-induced pathological changes in toll-like receptor 4 (TLR4)-lipid rafts of dorsal root ganglion neurons, which augment TRPV1-TLR4 interaction and TRPV1 sensitization. A-I binding protein alleviates paclitaxel-induced allodynia in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Paclitaxel (Taxol), a widely used chemotherapeutic agent, is known to induce both acute and chronic CIPN. Considering the role of OMDs in regulating voltage-gated ion channels and the previously reported role of paclitaxel in regulating membrane lipid domains 14,30,55,56 , we postulated that the paclitaxel-triggered neuropathy might be associated with alterations in the lipid domain organization of nociceptor DRG neurons. Using FLIM-FRET and the same CTxB-mediated labeling approach, our results revealed that overnight treatment using either a low concentration (10 nM) or a saturating concentration (1 μM) of paclitaxel resulted in a significant reduction in the FLIM-FRET efficiency of small DRG neurons (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Paclitaxel (Taxol), a widely used chemotherapeutic agent, is known to induce both acute and chronic CIPN. Considering the role of OMDs in regulating voltage-gated ion channels and the previously reported role of paclitaxel in regulating membrane lipid domains 14,30,55,56 , we postulated that the paclitaxel-triggered neuropathy might be associated with alterations in the lipid domain organization of nociceptor DRG neurons. Using FLIM-FRET and the same CTxB-mediated labeling approach, our results revealed that overnight treatment using either a low concentration (10 nM) or a saturating concentration (1 μM) of paclitaxel resulted in a significant reduction in the FLIM-FRET efficiency of small DRG neurons (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Inflammatory responses involve the reorganization of lipid domains, influencing cell signaling and immune responses. Moreover, emerging evidence suggests a link between lipid domains and chronic pain, particularly neuropathic pain that is often caused by nerve injuries (12, 13). In an animal model of chemotherapy-induced peripheral neuropathy and arthritis, targeting of lipid domains was effective to alleviate the pathological symptoms (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the human TG, KCNA1 expression was observed in neurons (percent = 49.1%) and to a much lesser extent in SGCs (percent = 1.7%) and SCs (percent = 3.1%), compared to its expression in mouse TG ( Figure 3C ). TLR4 (Toll-Like Receptor 4), which plays a role in pathogen recognition and innate immunity, is associated with pain ( Navia-Pelaez et al, 2022 ) and has been validated for expression in SGCs of human and rat TG ( Tse et al, 2014 ; Mitterreiter et al, 2017 ). The results of this study further verified that Tlr4 was significantly expressed in the SGCs of the human TG (20%) ( Figure 3C ), but was poorly expressed in mouse SGCs (1%) ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Apolipoprotein A-I binding protein (AIBP) is a new, selective regulator of inflammarafts. AIBP binds to TLR4 and thus facilitates cholesterol depletion primarily from cells expressing high surface levels of TLR4, such as dorsal root ganglia (DRG) nociceptive neurons and macrophages and activated spinal microglia [19 ▪▪ ,37]. Intrathecal administration of AIBP reverses established neuropathic pain in mouse models, with the therapeutic effect of a single dose lasting for over 2 months [18,19 ▪▪ ].…”
Section: Inflammarafts As a Therapeutic Targetmentioning
confidence: 99%